2014
DOI: 10.1080/1226508x.2014.930671
|View full text |Cite
|
Sign up to set email alerts
|

How Does Corruption Influence the Effect of Foreign Direct Investment on Economic Growth?

Abstract: We investigate the effect of Foreign Direct Investment (FDI) on economic growth by employing the data of 132 countries for the period from 1995 to 2008, considering the role of corruption in each country as an absorptive factor. The estimation results indicate that, although FDI alone does not promote economic growth, it has a significant effect on economic growth if the interaction term between FDI and corruption is considered. The threshold level of corruption separating the negative and positive effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…As noted above, several studies (e.g., Alfaro et al, 2004;Borensztein et al, 1998;Okada & Samreth, 2014) have used interaction terms in regression models to determine the existence of threshold effects and thus the role for spillover effects in the FDI-growth link. However, as emphasized by Girma (2005), Azman-Saini, Law, and Ahmad (2010), and Slesman et al (2015), this modelling strategy has the drawback of imposing the a priori restriction that spillovers are monotonically increasing (or decreasing) with absorptive capacity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted above, several studies (e.g., Alfaro et al, 2004;Borensztein et al, 1998;Okada & Samreth, 2014) have used interaction terms in regression models to determine the existence of threshold effects and thus the role for spillover effects in the FDI-growth link. However, as emphasized by Girma (2005), Azman-Saini, Law, and Ahmad (2010), and Slesman et al (2015), this modelling strategy has the drawback of imposing the a priori restriction that spillovers are monotonically increasing (or decreasing) with absorptive capacity.…”
Section: Methodsmentioning
confidence: 99%
“…Okada and Samreth (2014) consider the influence of corruption in the estimation of the FDI-growth regression using an interaction model and find that the threshold is around the 10th percentile of the least corrupt countries in their large sample of 130 countries over the period 1995-2008. Taking economic freedom as a threshold, Azman-Saini, Baharumshah, and Law (2010) use system generalized method of moments estimation with interaction effects in cross-country growth regressions for 85 countries over the period 1976-2004.…”
Section: Thresholds In the Fdi-growth Nexusmentioning
confidence: 99%
See 2 more Smart Citations
“…By investigating the effect of FDI on economic growth by employing the data of 132 countries for the period from 1995 to 2008. [20] found that although FDI alone does not promote economic growth, it has asignificant effect on economic growth if the interactionterm between FDI and corruption is considered. [21] examines the long-run impact of FDI and trade on economic growth in Ghana.…”
Section: Literature Reviewmentioning
confidence: 99%